2016
DOI: 10.1007/s13105-017-0552-6
|View full text |Cite|
|
Sign up to set email alerts
|

Adherence to Mediterranean diet is associated with methylation changes in inflammation-related genes in peripheral blood cells

Abstract: Epigenetic processes, including DNA methylation, might be modulated by environmental factors such as the diet, which in turn have been associated with the onset of several diseases such as obesity or cardiovascular events. Meanwhile, Mediterranean diet (MedDiet) has demonstrated favourable effects on cardiovascular risk, blood pressure, inflammation and other complications related to excessive adiposity. Some of these effects could be mediated by epigenetic modifications. Therefore, the objective of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(90 citation statements)
references
References 46 publications
2
84
0
Order By: Relevance
“…WBCs were immediately frozen at −80°C in buffy coat until use as described elsewhere (Arpón et al., 2016). Genomic DNA was extracted from WBC using the Master Pure DNA purification kit (Epicentre Biotechnologies, Madison, WI, USA) following instructions provided by the supplier.…”
Section: Methodsmentioning
confidence: 99%
“…WBCs were immediately frozen at −80°C in buffy coat until use as described elsewhere (Arpón et al., 2016). Genomic DNA was extracted from WBC using the Master Pure DNA purification kit (Epicentre Biotechnologies, Madison, WI, USA) following instructions provided by the supplier.…”
Section: Methodsmentioning
confidence: 99%
“…Bioactive substances, such as polyphenols, flavonoids, fish-derived oils and, in general, compounds enriched in the MedDiet, predominantly consisting of fruits and vegetables, have shown systemic benefits as preventive and curative molecules for metabolic diseases, cardiovascular risk and cancer [163][164][165][166]. Regular intake of MedDiet with coenzyme Q10 (Med + CoQ diet) has been associated with a lower expression of genes involved in inflammation, ER/oxidative stress and DNA damage in the peripheral blood mononuclear cells (PMBCs) of 63 volunteers [166].…”
Section: Precision and Accuracy: The Dartboard Of Nutritionmentioning
confidence: 99%
“…They found that Med + CoQ protects against ROS overproduction through mitigating the expression of oxidative, inflammatory and fibrotic markers, such as superoxide dismutase (SOD) 1/2 and matrix metalloproteinase (MMP) 9 [165]. Interestingly, either bariatric surgery or energetic restriction through MedDiet, used as obesity treatment, may also epigenetically modulate the expression of some of these markers influencing global DNA methylation and hydroxymethylation [164,167]. A high-protein diet improved hepatic steatosis in a mouse model of NAFLD independently of high fat and carbohydrate intake by increasing the lipid and branched-chain amino acid (BCAA) catabolism, enhancing mitochondrial oxidative ability and reducing fatty acid desaturation, ER stress and unfolded protein response [168].…”
Section: Precision and Accuracy: The Dartboard Of Nutritionmentioning
confidence: 99%
“…Thus, several experimental studies have investigated the epigenetic mechanisms underlying the health effects of certain nutrients and bioactive food components (Table 6). For instance, it was found that the anti-inflammatory effects of consuming a Mediterranean diet were related to hypermethylation of proinflammatory genes [84,85]. The administrations of polyunsaturated fatty acids positively modulated the expression of several miRNAs, which suppressed oncogenic and lipogenic genes [86,87].…”
Section: Diet and Epigenetic Signaturesmentioning
confidence: 99%